Hydrothermal Treatment of Empty Fruit Bunches to Enhance Fuel Characteristics - Hyeok Jin Kim; Chan Park; Rabin Nepal; Sea Cheon Oh (Energies, 2021)
Hydrothermal pretreatment of biomass can improve fuel characteristics based on the decomposition properties of subcritical water. Thus, this study used a hydrothermal treatment to improve the fuel characteristics of empty fruit bunches (EFBs), which are generated as waste after palm oil extraction. The experimental reaction temperature was increased from 180 °C to 250 °C at an interval of 10 °C and the mass ratios between the dry sample and water content were set to 1:8 and 1:16 so that the sample was sufficiently immersed. Additionally, the material properties of EFB under hydrothermal treatment conditions were investigated using mass and energy yields, elemental analysis, proximate analysis, thermogravimetric analysis, derivative thermogravimetry, and Fourier transform infrared spectroscopy analysis of the reaction products. As the reaction temperature increased, the fixed carbon content and heating value increased because volatile matter, including oxygen, was removed first, which is similar characteristics to coal. All analyses revealed that the water content exhibited little influence on EFB material properties since the samples were sufficiently immersed in water. Thus, it is not necessary to add more water that required for sample immersion for the hydrothermal treatment of EFB.